ANALISIS POTENSI DAN KELAYAKAN EKONOMI BUDIDAYA JAGUNG (Zea mays L) DI DESA PUUNDOHO KOLAKA UTARA, SULAWESI TENGGARA - Syamsuri Syamsuri; Hasria Alang (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2022)
Corn is the second food ingredient after rice, so its existence must be considered. One of the areas that cultivate corn as a livelihood is Puundoho Village. The purpose of this study was to analyze the potential and economic feasibility of corn cultivation in Puundoho Village, North Kolaka Regency. The results of this study are expected to contribute as a source of information, and also as consideration for determining the direction of the corn cultivation business in the region. The method of determining the location is done by purposive sampling. The variables studied were the potential and economic feasibility of corn cultivation in Puundoho Village. Determination of the sample is done through simple random sampling, to obtain 15 respondents. The data used are primary data obtained through observation and interviews. Data analysis was carried out by looking at revenue (TR: Q x P), income (I: TR-TC), and feasibility (R/C). The results showed that the income of corn cultivation farmers in Puundoho Village was 11,400,000, income was 8,070,000 and the R/C ratio was 3.4. This means that the corn cultivation business in the research location has economic potential and is feasible.